Adaptive Video Streaming Over Cognitive Radio Networks - Mohamed, Ala Eldin Omer (2017)
A Master of Science thesis in Electrical Engineering by Ala Eldin Omer Mohamed entitled, "Adaptive Video Streaming over Cognitive Radio Networks," submitted in January 2017. Thesis advisors are Dr. Mohamed Hassan and Dr. Mohamed El-Tarhuni. Soft and hard copy available.